2006
DOI: 10.1109/tmm.2006.884609
|View full text |Cite
|
Sign up to set email alerts
|

An Overlay Architecture for High-Quality VoIP Streams

Abstract: Abstract-The cost savings and novel features associated with Voice over IP (VoIP) are driving its adoption by service providers. Unfortunately, the Internet's best effort service model provides no quality of service guarantees. Because low latency and jitter is the key requirement for supporting high quality interactive conversations, VoIP applications use UDP to transfer data, thereby subjecting themselves to quality degradations caused by packet loss and network failures.In this paper we describe an architec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 30 publications
0
35
0
1
Order By: Relevance
“…Not only their CPU utilization is at 100%, but more importantly the queueing delays experienced by the running processes can be very significant -even up to several seconds between two consecutive accesses to CPU. This results in incorrect propagation time measurements and packet dropping due to incoming buffer overflow at the destination [19,20]. Moreover, the situation changes dynamically.…”
Section: ) Data Setsmentioning
confidence: 99%
“…Not only their CPU utilization is at 100%, but more importantly the queueing delays experienced by the running processes can be very significant -even up to several seconds between two consecutive accesses to CPU. This results in incorrect propagation time measurements and packet dropping due to incoming buffer overflow at the destination [19,20]. Moreover, the situation changes dynamically.…”
Section: ) Data Setsmentioning
confidence: 99%
“…Through mean opinion score (MOS) test results, it was found that FEC performed better than bit rate redundancy. In [4], localized packet loss recovery and rapid rerouting were used in the event of network failures for VoIP packets. The recovery protocols were deployed on the nodes of an application-level overlay network and did not require changes in the underlying infrastructure.…”
Section: Related Workmentioning
confidence: 99%
“…Performance Metrics: The effectiveness of the AWON architecture and the programming interface can be evaluated by measuring the quality of the content delivered to the end users under different network congestion conditions. For most real-time applications, application-specific metrics are used to measure quality of the content; for multimedia applications, these metrics include PESQ [1,19] for voice quality and PSNR [19] for video streaming. For the CASA application we use the standard deviation of the estimated sensed values (specifically, reflectivity and wind velocity) to evaluate quality of the radar data [6,7].…”
Section: Performance Evaluationmentioning
confidence: 99%
“…Overlay networks have been proposed to provide a range of useful services for enhancing QoS for Internet applications including bandwidth guarantees [1,3,11,19,22]. With overlay networking, application-aware processing can be implemented at intermediate nodes, thus significantly enhancing the ability of the application to adapt to network conditions and improve the QoS provided to the end users.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation